2013
DOI: 10.3389/fnhum.2013.00152
|View full text |Cite
|
Sign up to set email alerts
|

Testing the excitability of human motoneurons

Abstract: The responsiveness of the human central nervous system can change profoundly with exercise, injury, disuse, or disease. Changes occur at both cortical and spinal levels but in most cases excitability of the motoneuron pool must be assessed to localize accurately the site of adaptation. Hence, it is critical to understand, and employ correctly, the methods to test motoneuron excitability in humans. Several techniques exist and each has its advantages and disadvantages. This review examines the most common techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(200 citation statements)
references
References 86 publications
6
192
0
2
Order By: Relevance
“…demonstrated by decreased ICF) and increased motoneuronal excitability to offset cortical hypoexcitability, leading to increased SOL MEP amplitude. While in the future the use of corticospinal tract stimulation (Giesebrecht et al 2010;McNeil et al 2013) in conjunction with TMS would enable the determination of differential effects of vibration on both cortical and motoneuronal excitability, previous reports do not support differential vibration effects at the spinal and cortical levels. For instance, both unchanged F-waves (a means of assessing motoneuronal excitability) during vibration (Rollnik et al 2001) and unaffected postsynaptic excitability of SOL motoneurons during 25-Hz SOL vibration (Abbruzzese et al 1997) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated by decreased ICF) and increased motoneuronal excitability to offset cortical hypoexcitability, leading to increased SOL MEP amplitude. While in the future the use of corticospinal tract stimulation (Giesebrecht et al 2010;McNeil et al 2013) in conjunction with TMS would enable the determination of differential effects of vibration on both cortical and motoneuronal excitability, previous reports do not support differential vibration effects at the spinal and cortical levels. For instance, both unchanged F-waves (a means of assessing motoneuronal excitability) during vibration (Rollnik et al 2001) and unaffected postsynaptic excitability of SOL motoneurons during 25-Hz SOL vibration (Abbruzzese et al 1997) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In the current study, to further explore the role of these parameters in the diagnosis of RLS/WED, we aimed to assess the accuracy and compare the diagnostic values of each of these measures in a group of patients affected by primary RLS/ WED.…”
Section: Brief Summarymentioning
confidence: 99%
“…Although several methodologies have been used to estimate human motoneuron excitability, few of them are applicable to detect age-related differences during strong maximal muscle contractions (McNeil et al 2013). Indeed, this is an important aspect since it also reflects the changes of the fast twitch muscle fibers, which are closely linked to balance adjustments and fall prevention (Hvid et al 2010).…”
Section: Introductionmentioning
confidence: 99%